2018
DOI: 10.1097/mpg.0000000000001753
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heparin‐binding EGF‐like Growth Factor Polymorphisms With Necrotizing Enterocolitis in Preterm Infants

Abstract: Heparin-binding epidermal growth factor (EGF)-like growth factor (HB-EGF) protects the intestines from injury in experimental necrotizing enterocolitis (NEC). We hypothesized that polymorphisms in the HB-EGF gene lead to low HB-EGF production in peripheral blood and increased risk of NEC in the Chinese Han population. To test this hypothesis, 30 NEC patients and 80 control subjects were selected. Five HB-EGF single-nucleotide polymorphisms (SNPs) and its plasma levels were measured by genotyping and enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
1
0
4
Order By: Relevance
“…Другой сходный маркер, оценивающий активность нейтрофильного воспаления -липокалин-2 (LCN2), высокая диагностическая значимость которого была вначале продемонстрирована для острого повреждения почек [22].…”
Section: маркеры локального нейтрофильного воспаленияunclassified
See 3 more Smart Citations
“…Другой сходный маркер, оценивающий активность нейтрофильного воспаления -липокалин-2 (LCN2), высокая диагностическая значимость которого была вначале продемонстрирована для острого повреждения почек [22].…”
Section: маркеры локального нейтрофильного воспаленияunclassified
“…В настоящее время его диагностическая ценность показана при воспалительных заболеваниях кишечника среди взрослых. Причем активность LCN2 коррелировала с активностью кальпротектина [22].…”
Section: маркеры локального нейтрофильного воспаленияunclassified
See 2 more Smart Citations
“…55 The protective role of HB-EGF is thought to be mediated by increased intestinal blood flow, decreased apoptosis, and increased enterocyte migration and proliferation. 56 Ma et al 30 measured polymorphisms of HB-EGF in 30 NEC patients and 80 controls and found that rs4912711 SNP was associated with increased NEC. They also measured plasma levels of HB-EGF and found it to be decreased in NEC infants with the rs4912711 SNP, providing additional evidence that the identified SNP is potentially important.…”
Section: Candidate Gene Approachmentioning
confidence: 99%